Pengaruh Pemikiran Ekofeminisme Dewi Candraningrum terhadap Gerakan Akar Rumput Masyarakat Kendeng - Ayu Pawitri, Si Luh; Pramana, Gede Indra; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2021)
ABSTRACT This research aims to discuss the emergence of ecofeminism in Indonesia through Dewi Candraningrum's activism. The author tries to analyze the ecofeminism of Dewi Candraningrum and its influence on the Kendeng grassroots movement by using concepts such as habitus, field, capital, and doxa. By using participant observation methods, this research consisting of the emergence of ecofeminism thinking of Dewi Candraningrum can be traced through the history of her social trays which also related to the habitus or her daily life. Dewi Candraningrum's habitus was marked by the term of orthodoxy that can be seen from Kartini Kendeng's narrative conversion. In addition, the heterodoxy arose from the cultural capital and symbolic capital of Dewi Candraningrum which encouraged the mainstreaming of ecofeminism in Indonesia. This research also shows the holistic relationship between ecofeminism thinking and the Kendeng grassroots movement. Keywords: Habitus, Ecofeminism, Dewi Candraningrum, Kendeng’s Movement